2023
DOI: 10.1055/s-0043-1771375
|View full text |Cite
|
Sign up to set email alerts
|

Brief Overview of Clinical Evidence for Homeopathic Interventions in the Management of COVID-19 Patients

Daniel M.O. Campos,
Maria K. Silva,
Gabriel C.F. Morais
et al.

Abstract: This document was downloaded for personal use only. Unauthorized distribution is strictly prohibited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Campos et al present a brief overview of the literature up to May 2023 on medicines that have been most frequently used in reports of homeopathic management of COVID patients. 6 At the other end of the spectrum, Dr Parker Pracjek and co-authors focus on the rare and unusual COVID symptoms identified in patients managed by a group of homeopathic practitioners in the United States: the recommended remedy was commonly one associated with genus epidemicus prescribing. 7 Both these latter papers have been added to our virtual special issue, Homeopathy and COVID-19 , which now features 36 articles published in Homeopathy since the start of the pandemic.…”
mentioning
confidence: 99%
“…Campos et al present a brief overview of the literature up to May 2023 on medicines that have been most frequently used in reports of homeopathic management of COVID patients. 6 At the other end of the spectrum, Dr Parker Pracjek and co-authors focus on the rare and unusual COVID symptoms identified in patients managed by a group of homeopathic practitioners in the United States: the recommended remedy was commonly one associated with genus epidemicus prescribing. 7 Both these latter papers have been added to our virtual special issue, Homeopathy and COVID-19 , which now features 36 articles published in Homeopathy since the start of the pandemic.…”
mentioning
confidence: 99%